2012
DOI: 10.1039/c2nr32584e
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-riveted Pt catalyst supported on nanocapsule MWCNTs–Al2O3 with ultrahigh stability for high-temperature proton exchange membrane fuel cells

Abstract: Pt catalyst supported on nanocapsule MWCNTs-Al(2)O(3) (multi-walled carbon nanotubes, MWCNTs) catalyst has been prepared by microwave-assisted polyol process (MAPP). The results of electrochemical measurements show that the nanocapsule Pt/MWCNTs-Al(2)O(3) catalyst has higher activity due to more uniform dispersion and smaller size of Pt nanoparticles, and higher stability ascribed to the stronger metal-support interaction (SMSI) between Pt nanoparticles and nanocapsule support than in Pt/MWCNTs. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…For instance, If the support surface is SrTiO 3 (001), the encapsulated outmost layer is identified as a non-commensurate TiO x (Silly & Castell, 2005). Considering that the noble metal, particularly Pt, supported by the conventional TiO 2 and modified supports, has been receiving wide attention in terms of the SMSI effect, as shown in Table 1 (Liu et al, 2010;Zhu et al, 2011;Bidaoui et al, 2012;Jiang et al, 2012;Yao et al, 2012;Chang et al, 2013;An et al, 2014;Jia et al, 2014b;Kumar & Ramani, 2014). The relevant characterization includes TEM coupled with other methods, such as XPS, XRD, etc.…”
Section: Real-space Tem Observationmentioning
confidence: 99%
“…For instance, If the support surface is SrTiO 3 (001), the encapsulated outmost layer is identified as a non-commensurate TiO x (Silly & Castell, 2005). Considering that the noble metal, particularly Pt, supported by the conventional TiO 2 and modified supports, has been receiving wide attention in terms of the SMSI effect, as shown in Table 1 (Liu et al, 2010;Zhu et al, 2011;Bidaoui et al, 2012;Jiang et al, 2012;Yao et al, 2012;Chang et al, 2013;An et al, 2014;Jia et al, 2014b;Kumar & Ramani, 2014). The relevant characterization includes TEM coupled with other methods, such as XPS, XRD, etc.…”
Section: Real-space Tem Observationmentioning
confidence: 99%
“…These metals are, however, very expensive (average price is 40 E/g against 2 E/g for Ru for example [from http://www.platinum.matthey.com/prices/price-charts/]), are available in low amounts on earth (37 ppb in the Earth's crust), and are nonbiodegradable. Extensive research has aimed at decreasing the Pt content (for a review see [5] ), such as: 1) nanostructuration of the catalysts, [6,7] 2) use of alloys or heterostructures, [8][9] 3) nanostructuration and treatment of the carbon support, [10][11][12][13] 4) use of noncarbon matrixes such as conducting polymers, [14] and 5) use of semiconductive transitionmetals. [15] Furthermore, platinum catalysts are readily poisoned by very low levels of CO and S (0.1 % of CO is sufficient to decrease one hundred fold the catalytic activity of Pt in ten minutes), thus requiring extensive H 2 purification.…”
Section: Introductionmentioning
confidence: 99%
“…It also can be seen that the binding energy of Pt(0) for Pt/CeO 2 -20 wt% shows a higher shift about 0.23 eV in comparison with Pt/CeO 2 , which is likely ascribed to the reason that the formation of C-N bonds on the support surface can intensify the electron withdrawing effect against Pt and strengthen the metal-support interaction between Pt nanoparticles and the support [31]. And another critical found is that the content of functional species Pt(0) in the Pt/CeO 2 -20 wt% catalyst increases by 9.43 %, while Pt(IV) decreased by 4.99 % compared with Pt/CeO 2 , which leads to greatly enhanced durability for Pt/CeO 2 coated with PVP catalyst, [32] so it can be concluded that the nitrogen-doped carbon is successfully incorporated onto CeO 2 .…”
Section: Resultsmentioning
confidence: 96%